A COMPARATIVE OBSERVATIONAL STUDY ON EFFECTIVENESS OF PROBIOTICS AND ANTIBIOTICS IN BACTERIAL VAGINOSIS - Sowmya B; Dattatreya Kar; Rajashree Panigrahy; Basanta Pati (Universitas Airlangga, 2023)
Introduction: Bacterial vaginosis is a common vaginal dysbiosis in women of reproductive age. Bacterial vaginosis is a dysbiosis characterized by a reduction of Lactobacillus species, such as L. crispatus, L. gasseri, and L. Jensenii. Anti-microbial resistance of BV pathogens and low long-term cure rates have been increasing in the few years. Aim: Probiotics are proposed as an alternative treatment for BV applying live micro-organisms with the capacity to confer health benefits to the patient. Methods: Patients with white discharge per vagina with or without foul smell, and itching visiting Obstetrics and Gynecology OPD are subjected to Amsel criteria. Those test positive for 3 out of 4 are diagnosed to have bacterial vaginosis and were enrolled in the study. Result: Highest prevalence of bacterial vaginosis was at the age group of 26-30 years (28%), with the lowest prevalence (16%) above 40 years of age. Among group A (probiotics), 68% and 32% of women were in not working and working groups, respectively, when compared with group B (antibiotics), 64% and 36% of women were in not working and working groups. Nulligravida (28% and 32%), Singleton Pregnancy (32% and 16%) in Group A and Group B. We observed that patients treated with both antibiotics (50%) and probiotics (50%) had similar recurrence rates of BV. Conclusion: Hence it would be prudent to prefer probiotics in patients with BV, as they colonize other normal commensals and have similar efficacy as that of antibiotics. The other beneficial factors of probiotics include acceptability to patients and nil side effect profile.